The Effectiveness of Enforcing the Polluter Pays Principle as an Ecological Restoration Mechanism in Environmental Disputes in Indonesia - Faza Pauzia Hermawan; Milda Kurnia Herawati; Raenita Aulia Dewi; Tierra Kresna (International Journal of Law and Society, 2026)
Environmental pollution and degradation remain serious issues in Indonesia, causing significant impacts on ecosystems and the social life of communities. One of the fundamental principles in environmental law aimed at ensuring ecological restoration is the Polluter Pays Principle (PPP), which obliges polluters to bear all costs arising from environmental pollution or damage caused by their activities. This study aims to analyze the effectiveness of enforcing the Polluter Pays Principle as a mechanism for ecological restoration in resolving environmental disputes in Indonesia. The research employs a normative legal research method using statutory and conceptual approaches. The findings indicate that although the Polluter Pays Principle has been normatively adopted in Law Number 32 of 2009 on Environmental Protection and Management, its implementation in practice remains suboptimal. Major obstacles include weak law enforcement, power imbalances between business actors and affected communities, lack of transparency in the use of compensation funds, and limited public participation in environmental restoration processes. Therefore, strengthening regulatory frameworks, enhancing the capacity of law enforcement institutions, and adopting a restorative justice approach are necessary to ensure that the Polluter Pays Principle functions effectively in achieving ecological restoration and environmental justice in Indonesia.